Budding Yeast SLX4 Contributes to the Appropriate Distribution of Crossovers and Meiotic Double-Strand Break Formation on Bivalents During Meiosis - Higashide, Mika (G3 (Bethesda), 2016)
The number and distribution of meiosis crossover (CO) events on each bivalent are strictly controlled by multiple mechanisms to assure proper chromosome segregation during the first meiotic division. In Saccharomyces cerevisiae, Slx4 is a multi-functional scaffold protein for structure-selective endonucleases, such as Slx1 and Rad1 (which are involved in DNA damage repair), and is also a negative regulator of the Rad9-dependent signaling pathway with Rtt107. Slx4 has been believed to play only a minor role in meiotic recombination. Here, we report that Slx4 is involved in proper intrachromosomal distribution of meiotic CO formation, especially in regions near centromeres. We observed an increase in uncontrolled CO formation only in a region near the centromere in the slx4∆ mutant. Interestingly, this phenomenon was not observed in the slx1∆, rad1∆, or rtt107∆ mutants. In addition, we observed a reduced number of DNA double-strand breaks (DSBs) and altered meiotic DSB distribution on chromosomes in the slx4∆ mutant. This suggests that the multi-functional Slx4 is required for proper CO formation and meiotic DSB formation.